KALIMAT INTEROGATIF DALAM BUKU TEKS BAHASA INDONESIA KELAS XI EDISI REVISI 2017 - Tika Melinda; Mukhlish Ainuri (CARAKA, 2020)
This study aims to describe the question words, types, and interrogative sentence patterns in Indonesian textbooks Class XI Revised Edition 2017. This type of research is qualitative. The analysis method is a method of sharing with marking reading techniques and analysis of sentence constituent function functions. This method is presented informally. The results of this study are (1) question words include: apa(kah), siapa(kah), mengapa, kenapa, bagaimana(kah), mana(kah), di mana, dari mana, kapan(kah), berapa, and bukan; (2) types of asking for a yes-no answer, asking for information about one of the elements of the sentence, asking for a reason, asking for an opinion, and verifying; (3) the pattern is (a) (Kt.Tny)+S+P+(O)+(Ket), (b) +Adv+-kah+S+P+O+(Ket), (c) +P+-kah+S+Ket, dan (d) +S+P+(O)+(Pel)+(Ket), Kt.Tny.Â